Brushless DC Motor Speed Control Using Single Input Fuzzy PI Controller - N. N. Baharudin; S. M. Ayob (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Brushless DC (BLDC) motor is more reliable than classic DC motor with higher efficiency. Commonly used conventional linear controller such as PI, PID and PD controller. FLC is considered a replacement to conventional controller due to advantages on non-linear system. Hybrid controller e.g Fuzzy PI controller is developed to cope with drawback of both controller. Simplification of FLC in previous study is the pioneer of the idea of proposed method. Single-Input Fuzzy PI Controller (SIFPIC) is a hybrid controller that combines advantages of linear PI controller and fuzzy controller in one control structure. Since it is a single input based fuzzy controller, it yields simpler design and tuning process.  Simulation is done using MATLAB/Simulink and the performance is observed through speed response under several conditions namely constant speed, changing seed and changing load torque. The performance of SIFPIC is compared with conventional PI and fuzzy PI controller. SIFPIC is as expected produced a response similar with the conventional fuzzy PI controller with both fuzzy based controller produce response with better dynamic.